Color tuning of Bi3+-doped double-perovskite Ba2(Gd1−x, Lux)NbO6 (0 ≤ x ≤ 0.6) solid solution compounds via crystal field modulation for white LEDs. Issue 43 (6th July 2020) - Tang, Xufang; Jin, Dingfeng; Zhao, Jun; Jin, Min
Abstract : Nowadays, rare-earth-free color-tunable solid solutions are receiving great attention. Abstract : Nowadays, rare-earth-free color-tunable solid solutions are receiving great attention. Here, we synthesize a type of double-perovskite Ba2 (Gd1− x, Lu x )NbO6 :Bi 3+ (0 ≤ x ≤ 0.6) solid solution compound using high temperature solid state reaction. The structural phase purity and photoluminescence (PL) properties of the samples are characterized by powder X-ray diffraction (XRD), density functional theory (DFT) calculations, UV-visible diffuse reflectance spectroscopy and PL spectroscopy. Structural analysis shows that all the samples are crystallized in the double-perovskite structure with a cubic space group of Fm 3̄ m . Moreover, with the increase of Lu 3+ content, the XRD positions are gradually shifted toward higher diffraction angles, indicating the shrinkage of the crystal lattice. Our PL results show that the Ba2 (Gd1− x, Lu x )NbO6 :Bi 3+ solid solutions can show Bi 3+ tunable emissions from 462 nm to 493 nm and excitation peaks from 363 nm to 390 nm with the increase of Lu 3+ content from 0 to 0.6, owing to the crystal field modulation around the Bi 3+ ion. In addition, the blue-shift of the host excitation peaks is also observed, which is ascribed to the increase of bandgap energies ( i.e., from 3.01 eV to 4.14 eV based on the DFT calculations). Besides, due to the closer structural rigidity induced by the replacement of larger Gd 3+ ions with smaller Lu 3+ ions, the Ba2 (Gd1− x, Lu x )NbO6 :Bi 3+ solid solutions show an increase of Bi 3+ emission intensity and QE values followed by a subsequent decrease. As a result, the highest QE value, which corresponds to Ba2 Gd0.8 Lu0.2 NbO6 :Bi 3+, is 49%. Finally, by coating this optimal blue phosphor and the red CsPb(Br0.4 I0.6 )3 phosphor on a commercial UV LED chip, a white LED device with a color temperature (CT) of 3633 K, CIE value at (0.381, 0.379), color rendering index (CRI) of 78.4, and luminous efficiency of 48 lm W −1 is achieved.